New sorbents for determining the quality of alcoholic beverages by chromatographic analysis - T. N. Kordzakhia; M. G. Zautashvili; L. G. Eprikashvili; N. V. Pirtskhalava; M. A. Dzagania; G. P. Tsintskaladze; T. V. Sharashenidze; A. G. Rakviashvili (Хімія, фізика та технологія поверхні, 2024)
A new universal gas-chromatographic method of identification of toxic impurities is proposed in order to improve the quality indicators of alcoholic beverages. Application of chromatographic methods in wine making is characterized by some peculiarities, which is stipulated from one hand by substance characteristics as they are and from the other by changes in chromatographic methods possibilities. The method allows to determine the quality and chemical composition of the alcoholic beverages, which to some extent determines the possibility of regulating its quality on a scientific basis. Modification of the methods presented in the work is based on utilization of packed and capillary-packed columns. They are mainly usable for quantitative analysis, are stable, characterized with good reproducibility and can be used as long as a year and more. Several immobile liquid phases – PEG-300, PEG-400, PEG-20000,       SE-30 and polymeric sorbent  – Poropak-Q, Separon-CDA – were tested in order to determine the optimum conditions for chromatographic separation. To achieve this goal, a combined chromatographic packed column (Poropak-Q+SE-30) based on the principles of adsorption and distribution chromatography was created. Chromatography of a twelve-component 0.1 % graded mixture (acetone, acetic aldehyde, butanone-2, methanol, propanol-2, ethanol, butanol-2, propanol-1, isobutanol, butanol-1, crotonaldehyde, isopentanol) was carried out. The analyses were performed in both isothermal and temperature-programmed modes.